SCIENCE LITERACY ANALYSIS OF PHYSICS INSTRUCTIONAL MATERIAL FOR SENIOR HIGH SCHOOL GRADE IN PADANG CITY BASED ON DIGITAL TECHNOLOGY - Sinthia Dwi Jayanti; Ratnawulan -; Asrizal -; Silvi Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2023)
The development of science and technology in the era of the industrial revolution 4.0 is increasing rapidly and has its own challenges for the world of education. Existing and growing digital technology supports all the demands of this curriculum. The internet can be accessed by anyone, including students. However, some of the information they obtained cannot be confirmed. For this reason, literacy skills are needed for students to be able to sort information. Indonesia's science literacy condition is currently lagging far behind compared to other countries, as can be seen throughPISA. The purpose of this study was to determine the emergence of the scope of science literacy in physics instructional material for class X senior high school in Padang city. This type of research used descriptive research with a qualitative approach. The research method is the document analysis method. The research population is all instructional material used by class X high school students in the city of Padang. The research samples are three instructional material used by high school class X students in Padang City. The research results (1) science as a body of knowledge by 90.93%, 59, and 80%, (2) science as a way of investigating by 21.85%, 21.24% and 4.57%, (3) science as a way of thinking by 24.07%, 6.42% and 4.57%, and (4) the interaction of science, technology and society by 3.33%, 0.76% and 4.57%. This shows that it is necessary to develop these instructional material so that there is a science literacy component.